Activation of the semispinalis cervicis and splenius capitis with cervical pulley exercises. (August 2017) - Rivard, Jim; Unsleber, Cindy; Schomacher, Jochen; Erlenwein, Joachim; Petzke, Frank; Falla, Deborah
Abstract: Study design: Quasi-Experimental. Objective: To assess the activation of semispinalis cervicis (d-SSC) and splenius capitis (s-SC) muscles, and the activation between the two during neck pulley and free weight exercises. Background: Altered activation of cervical extensors may occur with neck pain, suggesting that exercises should be designed to target these muscles. Methods: d-SSC and s-SC activity was recorded unilaterally with intramuscular electromyography from healthy volunteers during cervical isometric exercises: 1) extension with a pulley rope angled from incline to vertical, 2) extension with right, left and central forehead hanging weight, and 3) rotation with pulley rope angled from incline to decline. Results: Extension against a vertical force led to greater activation of d-SSC (P < 0.001) and s-SC (P < 0.001) compared to the inclined, declined and horizontal pulley. With each of these conditions, amplitude of muscle activity was higher for the d-SSC compared to the s-SC muscle (P < 0.0001). Extension with free weight hanging on right, left or central forehead, showed no differences across conditions, although in each condition, the d-SSC amplitude was higher than the s-SC. For cervical rotation, the declined pulley led to the greatest activation of both muscles (P < 0.05). Higher levels of activity were observed for the s-SC compared to the d-SSC (P < 0.01) for all rotation conditions. Conclusion: A vertical resistance during an extension exercise or a declined resistance during cervical rotation, increased neck extensor activation. The results from this preliminary study provide guidance for future work on the exploration and development of low-load exercise design for patients with neck pain disorders. Highlights: Neck extensor activation changes with the line of resistance during exercise. A more vertical line of action was preferable during cervical extension. A declined pulley was superior during cervical rotation. The results provide guidance for exercise design for patients with neck disorders.